Design of an ultrabright biosensor for dynamic imaging of kinase activity in cells - Xiaoquan Li; Sophia K. Tan; Chan-I Chung; A. Katherine Hatstat; Qian Zhao; Jingyu Luo; William F. DeGrado; Xiaokun Shu (Proceedings of the National Academy of Sciences, 2026)
Protein kinases regulate almost every major signaling pathway. Visualizing spatiotemporal dynamics of kinase activity is thus essential to understand cell signaling. Here, we report a de novo–designed activity reporter of kinase, dubbed NOVARK, which contains a single polypeptide chain with multiple modular motifs that act as specific kinase substrates and reporters. NOVARK undergoes phosphorylation-induced higher-order assembly, which are detectable as ultrabright green fluorescent protein (GFP) droplets with a large dynamic range. We designed versions of NOVARK that rapidly and reversibly report intracellular activity of protein kinase A, C, and extracellular signal-regulated kinase (ERK) following stimulation/inhibition by upstream G protein-coupled receptor (GPCR) agonists. Our work provides a generalizable platform that enables the design of ultrabright biosensors for illuminating dynamic architecture of kinase signaling.